Hospital incident command system, the pillar of COVID-19 outbreak response: An experience from Patan Hospital, Nepal (Journal of Patan Academy of Health Sciences, 2020)
In times of disaster, hospital’s preparedness for disaster and response plan contributes significantly to better functioning of the hospital and reducing mortality and morbidity. Activating Hospital incident command system in a timely manner in Patan Hospital has showed how the hospital is better prepared to handle this epidemic outbreak.